Temporal Evolution of Left Main Coronary Artery Stenosis De Novo Presentation: Trends in Coronary Angiography and Clinical Characteristics (LM-EVOLUTION Study) - Jakub Chmiel; Kacper Miłosz Książek; Jagoda Dradrach; Grażyna Wnuk; Krzysztof Piotr Malinowski; Karol Musiał; Władysław Dąbrowski; Łukasz Czyż; Paweł Iwaszczuk; Kenneth Rosenfield; Piotr Musiałek (Journal of Interventional Cardiology)
Conclusions: In consecutive patients presenting with de novo LM stenosis, angiographic SS showed a statistically significant negative trend over a decade, driven primarily by a reduction in non-LM-SS. Our findings are consistent with an increase in the proportion of patients presenting with LM stenosis amenable to first-line percutaneous (rather than surgical) management (LM-EVOLUTION study).